Psychological Manipulation and Cyber Identity: A Critical Examination of Cyberbullying’s Poetics in Backlash - Jihad, Ahmed Natiq; Al- Doory, Awfa Hussein (Journal of Tikrit University for Humanities, 2025)
Cyberbullying, a pervasive and damaging form of harassment, has become an urgent issue in the digital age, affecting millions of adolescents worldwide. Sarah Darer Littman’s novel “Backlash” delves into this complex and often devastating phenomenon, providing a stark and insightful exploration of its effects on young people. This study examines the theme of cyberbullying in “Backlash,” analyzing its portrayal, the psychological and social impacts on the characters, and the broader implications for readers and society. The study relies heavily upon the conceptual framework of psychological manipulation which is a type of social influence that aims to change the behavior or perception of others through abusive, deceptive, or underhanded tactics. By advancing the interests of the manipulator, often at another’s expense, such methods could be considered exploitative, abusive, devious, and deceptive. The study is analytical , it follows a new critic approach that focuses on the way the content of any literary work is represented by a particular form . Furthermore, it follows a structural approach as it highlights the layers of the examined work so as to foster its discourse which aim at raising the collective consciousness about cyber bullying and its after effect.